Technique for Huynen–Euler decomposition. Issue 13 (2nd June 2017) - Dallmann, T.; Heberling, D.
Abstract : We describe a novel approach to extract Huynen–Euler parameters from a polarimetric scattering matrix. In contrast to existing methods, this technique is able to determine the full set of parameters while requiring the handling of only four special cases via case distinction. Results from a Monte‐Carlo simulation show that the maximum error caused by the decomposition is close to floating point accuracy.